2001
DOI: 10.1890/1051-0761(2001)011[1472:rgdiet]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Genetic Diversity in Eelgrass Transplantations Affects Both Population Growth and Individual Fitness

Abstract: The transplantation of eelgrass (Zostera marina) for mitigation results in reduced genetic diversity among individuals and populations in southern California, the Chesapeake Bay, and New Hampshire. Although genetic variation determines the potential for eelgrass to adapt to the rapidly changing environment in its coastal and estuarine habitats, genetic considerations are not currently included in mitigation and restoration policy. I investigated where and how genetic diversity is lost during eelgrass transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(33 citation statements)
references
References 82 publications
0
29
1
3
Order By: Relevance
“…Unlike several previous experimental studies in marine systems (Allison, 2004; Reusch et al, 2005; Williams, 2001), our mensurative study found that the rate of post-disturbance recovery was not significantly related to taxonomic richness (Table 1, Fig. 2).…”
Section: Discussioncontrasting
confidence: 97%
“…Unlike several previous experimental studies in marine systems (Allison, 2004; Reusch et al, 2005; Williams, 2001), our mensurative study found that the rate of post-disturbance recovery was not significantly related to taxonomic richness (Table 1, Fig. 2).…”
Section: Discussioncontrasting
confidence: 97%
“…Data from specific publications were further filtered and processed to partition multiple, independent datasets within a publication into separate studies [33,[44][45][46][47][48]; to exclude natural colonization sites or revegetation sites where natural individuals were still present [38,47,49]; to include individual site estimates rather than across site averages [39,50]; to include 'large' rather than 'small' natural remnants as natural site comparisons [51]; to ensure a single estimate per genetic metric per site [52]; and in one case to include natural stand data from a complementary study [53,54] (see Supplementary Methods in the electronic supplementary material for more detail).…”
Section: Literature Review and Analysismentioning
confidence: 99%
“…Poor translocation methods added to bad environmental conditions can cause poor survival rates in the beginning of the restoration efforts [48]. The other possible cause is the use of plants with no genetic background, which can lead to low genetic diversity, due to genetic drift or high genetic load of source population [49].…”
Section: Mangrove Restoration Practices Caused Bottleneck In Introducmentioning
confidence: 99%